2007
DOI: 10.1002/chem.200600916
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Range‐Distance NMR Effects in a Protein Labeled with a Lanthanide–DOTA Chelate

Abstract: A two-thiol reactive lanthanide-DOTA (1,4,7,10-tetraazacyclododecane-N,N',N'',N'''-tetraacetic acid) chelate, CLaNP-3 (CLaNP=caged lanthanide NMR probe), was synthesized for the rigid attachment to cysteine groups on a protein surface, and used to obtain long-range-distance information from the {15N,1H} HSQC spectra of the protein-lanthanide complex. The DOTA ring exhibits several isomers that are in exchange; however, single resonances were observed for most amide groups in the protein, allowing determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 74 publications
3
81
0
1
Order By: Relevance
“…Gadolinium-containing CLaNP was tested previously for its distance-dependence effects on a protein. 19 A high degree of correlation was obtained between the distances derived from paramagnetic relaxation enhancements (PRE) and those from the crystal structure. Three surface-exposed double Cys mutants were engineered on NiR: N221C/A223C (NirA), T234C/A236C (NirB) and S333C/A336C (NirC), to serve as points of attachment of the paramagnetic probe.…”
Section: Paramagnetic Relaxation Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…Gadolinium-containing CLaNP was tested previously for its distance-dependence effects on a protein. 19 A high degree of correlation was obtained between the distances derived from paramagnetic relaxation enhancements (PRE) and those from the crystal structure. Three surface-exposed double Cys mutants were engineered on NiR: N221C/A223C (NirA), T234C/A236C (NirB) and S333C/A336C (NirC), to serve as points of attachment of the paramagnetic probe.…”
Section: Paramagnetic Relaxation Enhancementmentioning
confidence: 99%
“…17 Previously, we have shown that such bidentate complexes of Gd can provide reliable distance information on the basis of paramagnetic relaxation effects in the range of 20-30 Å from the metal. 18,19 Here, we show that by taking advantage of TROSY and perdeuteration, in combination with the use of paramagnetic NMR, an experimental structural model of the 152 kDa protein complex between NiR and Paz can be obtained. The results provide information about the nature of the interface and suggest paths for the interprotein electron transfer (ET).…”
Section: Introductionmentioning
confidence: 98%
“…The resulting set of long-range distance restraints, in combination with a few chemical shift perturbations, were sufficient to dock the proteins and yield an ensemble of pseudoazurin structures with an RMSD of 1.5 A ( Figure 6.5). The PREs extended to 35 A , which is a larger distance than is obtained for small proteins equipped with the same probe [10], because the larger t r of the complex results in larger paramagnetic effects (see Equation 6.2). This study shows the great potential to study large protein complexes with paramagnetic restraints.…”
Section: Structures Of Protein Complexesmentioning
confidence: 97%
“…We found the one-point method to produce reliable distance restraints between 20 and 30 A for a Gd 3 þ probe [10], with a precision of AE 3 A , see Figure 6.1. The range of distances that can be studied depends on the relaxation agent.…”
Section: Paramagnetic Dipolar Relaxation Enhancementmentioning
confidence: 99%
“…Dieser unerwünschte Effekt konnte durch verschiedene Modifikationen entscheidend verringert werden. [14] In unserem Fall war der DOTA-M8-Ytterbiumkomplex (Yb-M8; DOTA = 1,4,7,10-Tetraazacyclododecan-1,4,7,10-tetraessigsäure) [15] zielführend, um eine Erhçhung der Signaldispersion zu erreichen. Dieser kann bei der Komplexbildung mit verschiedenen Lanthanoiden durchaus zu einer Verdoppelung der Signale führen, bei der Verwendung von Ytterbium erreicht man aber eine fast vollständige Population von nur einem Isomer.…”
unclassified